2005
DOI: 10.1016/j.proci.2004.08.233
|View full text |Cite
|
Sign up to set email alerts
|

Transition from forward smoldering to flaming in small polyurethane foam samples

Abstract: Experimental observations are presented of the effect of flow velocity, oxygen concentration, and a thermal radiant flux, on the transition from smoldering to flaming in forward smoldering of small samples of polyurethane foam with a gas/solid interface. The experiments are part of a project studying the transition from smoldering to flaming under conditions encountered in spacecraft facilities, i.e., microgravity, low velocity variable oxygen concentration flows. Because the microgravity experiments are plann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 12 publications
2
33
1
Order By: Relevance
“…The reaction mechanism includes three pyrolysis reactions and four oxidation reactions. One of the oxidation reactions included is what has been referred to as "secondary char oxidation", which has been identified as the key step leading to transition to flaming [10], [12]. While the current focus is not to examine the transition from smoldering to flaming, the work establishes the framework to potentially do so in the future.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction mechanism includes three pyrolysis reactions and four oxidation reactions. One of the oxidation reactions included is what has been referred to as "secondary char oxidation", which has been identified as the key step leading to transition to flaming [10], [12]. While the current focus is not to examine the transition from smoldering to flaming, the work establishes the framework to potentially do so in the future.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that non-fired retarded (NFR) polyurethane foam is susceptible to smoldering and transition to flaming [1,8,9]. In particular, Bar-Ilan et al conducted a study on forward smoldering and transition to flaming in NFR flexible polyurethane foam of density 26.5 kg/m 3 , using the same experimental apparatus as that in the present study.…”
Section: Introductionmentioning
confidence: 90%
“…The experimental apparatus is very similar to that used by Bar-Ilan et al for non-fire retarded polyurethane foam experiments [9], and a schematic is shown in (Fig. 1).…”
Section: Experiments Conceptmentioning
confidence: 99%
See 2 more Smart Citations